Two-stage multi-modal system for low frequency and wide bandwidth vibration energy harvesting - Ong, Zhi Chao; Ooi, Y.X.; Khoo, Shin Yee; Huang, Yu Hsi (Elsevier, 2020)
Wind power has gained interest of research over past decades as renewable energy solution. Vibration controller is usually installed to mitigate vibration while part of structural vibration is potential to be harvested as regenerative energy source using vibration energy harvester and supplied to vibration controller to create a self-powered system. This study aims to develop a novel two-stage multimodal piezoelectric cantilever energy harvester system design to harness vibration of low-frequency range (<10 Hz). The primary system consists of a height-adjustable fixture, two metallic cantilever beams with different tip mass to achieve low natural frequency whereas the secondary system consists of a cantilever piezoelectric bimorph plate. Prototype of the proposed design is fabricated, and the experimental results indicate that setting the gap at 1 cm between primary and secondary systems improves voltage generation by 82.83%–349.87%. The operational bandwidth of two-stage multimodal system is also extended to the range of 5.5 Hz–7.0 Hz. © 2019 Elsevier Ltd